Qualitative assessment of structural strength for thermoformed honeycomb sandwiched structures - Abdul Rashid, Marjuki (2015)
Honeycomb sandwiched structures is one of the most valued structural engineering innovations developed by the composites industry. Used extensively in automotive and aerospace technologies, the advanced material construction provides key benefits over conventional metal and structural designs by offering very low weight to power ratio, enhancing structural stiffness, improving durability and cost-effective alternatives. This project involved designing a Thermoforming prototype mould for thermoplastic based honeycomb cores based on industrial general practices. Design consideration includes the sizing of hexagonal cell and low in situ cutting forces. Proprietary polypropylene sheet was thermoformed on wire-cut EDM machined Aluminium (P20) mould. It was found that the 0.006sq.m sandwiched structured fibreglass with 0.001m thickness honeycomb cores stabilized at 0.2MPa compression surface forces.